Amplification of LDH gene from Indian strains of Plasmodium vivax - Ritu Berwal, N. Gopalan, Kshitij Chandel, Shri Prakash ,K. Sekhar (Journal of Vector Borne Diseases, 2006)
Background & objectives: Plasmodium vivax is geographically widespread and responsible for >50% of malaria cases in India. Increased drug resistance of the parasite highlights the immediaterequirement of early and accurate diagnosis as well as new therapeutics. In view of this, the presentstudy was undertaken to amplify P. vivax (Indian strains) lactate dehydrogenase gene (PvLDH)which has been identified as a good target for antimalarials as well as diagnostics.Methods: P. vivax infected clinical blood samples were collected from southern part of India andwere tested with established diagnostic parameters (ICT, Giemsa staining). Total DNA was extractedfrom blood samples and subjected to PCR using two sets of primers, one for the amplification of fullPvLDH gene (951bp) and the other for a partial PvLDH gene fragment (422bp), covering a variableantigenic region (140aa) as compared to other plasmodial species.Results & conclusion: PCRs for both the full and partial gene targets were optimised and found to beconsistent when tested on several P. vivax positive clinical samples. In addition, full gene PCR wasfound to specifically detect only P. vivax DNA and could be used as a specific molecular diagnostictool. These amplified products can be cloned and expressed as a recombinant protein that might beuseful for the development and screening of antimalarials as well as for diagnostic purposes.